Optimality Analysis of Vowel Harmony in ÀÍKA (American International Journal of Education and Linguistics Research, 2018)
This paper gives an Optimality Theory (Henceforth OT) account of advanced tongue root (ATR) vowel harmony in ÀÍKA, an Edoid language that consists of four speech forms spoken in Akoko-Edo area in Nigeria. The ATR harmony manifests within as well as across morpheme boundaries. The ATR harmony across morphemes affects the subject pronouns, prefixes as well as demonstrative pronouns because they are underspecified for ATR value while object pronouns are underlyingly specified. It is further noted that ATR has a morphological effect on the items it affects as it triggers phonological allomorphy in them. In addition to right-to-left spreading analysis in the literature (Abiodun 1999, Ibikunle 2014, and 2016), this research further reveals that there are pieces of evidence for left-to-right spreading of harmonic value. More importantly, this analysis shows that OT is viable and problem-solving efficient compared with the Non-Linear or traditional generative account on Vowel Harmony system of the language.